2017
DOI: 10.1007/s00520-017-3817-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indomethacin oral spray for the treatment of oropharyngeal mucositis-induced pain during anticancer therapy

Abstract: The present IM spray is an effective and safe preparation for pain relief and can be used as an alternative therapeutic option for oropharyngeal mucositis in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Functional impact include difficulties in swallowing, speaking and eating, food restriction, sense of oral dryness and pain, which resulted in lack of food enjoyment [5,26,28]. Table 4 presents our findings on the management of some oral conditions among palliative patients and their effectiveness [11,15,17,[19][20][21][22][23] Our study revealed that the common management options for xerostomia are drug and medical treatments [15], lubricating lips and mucosa [17], acupuncture [19], and standard oral care which improved dry mouth (in 80% or more) of the patients [11]. For candidiasis, a single-dose fluconazole 150 mg via mouth was found to be very effective as the symptoms decreased significantly (P < 0.001) in most patients [20], and local antifungal treatments were reported to be efficacious in 78.1% of the patients [23].…”
Section: Common Oral Conditions Among Palliative Patientsmentioning
confidence: 95%
See 3 more Smart Citations
“…Functional impact include difficulties in swallowing, speaking and eating, food restriction, sense of oral dryness and pain, which resulted in lack of food enjoyment [5,26,28]. Table 4 presents our findings on the management of some oral conditions among palliative patients and their effectiveness [11,15,17,[19][20][21][22][23] Our study revealed that the common management options for xerostomia are drug and medical treatments [15], lubricating lips and mucosa [17], acupuncture [19], and standard oral care which improved dry mouth (in 80% or more) of the patients [11]. For candidiasis, a single-dose fluconazole 150 mg via mouth was found to be very effective as the symptoms decreased significantly (P < 0.001) in most patients [20], and local antifungal treatments were reported to be efficacious in 78.1% of the patients [23].…”
Section: Common Oral Conditions Among Palliative Patientsmentioning
confidence: 95%
“…Studies reporting on oral conditions among palliative patients are summarized in Table 1. Of the included studies, 16 were quantitative studies [5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24], and 3 were qualitative studies [25][26][27] (Table 2).…”
Section: Characteristics Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, indomethacin, which has an analgesic effect, or allopurinol and rebamipide (RB), which have a free radical scavenging effect, are administered to treat stomatitis caused by chemotherapy and radiotherapy [8,[11][12][13][14][15][16][17][18][19]. Allopurinol has a good treatment effect on stomatitis; however, it interacts with fluorouracil, which decreases its anticancer effect, and it has been reported that there are restrictions to its administration [20,21].…”
Section: Introductionmentioning
confidence: 99%